Role of dietary protein in post-exercise muscle reconditioning - van Loon, L. J. C. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
Dietary protein ingestion after exercise stimulates muscle protein synthesis, inhibits protein breakdown and, as such, stimulates net muscle protein accretion following resistance as well as endurance type exercise. Protein ingestion during and/or immediately after exercise has been suggested to facilitate the skeletal muscle adaptive response to each exercise session, resulting in more effective muscle reconditioning. A few basic guidelines can be defined with regard to the preferred type and amount of dietary protein and the timing by which protein should be ingested. Whey protein seems to be most effective to increase post-exercise muscle protein synthesis rates. This is likely attributed to its rapid digestion and absorption kinetics and specific amino acid composition. Ingestion of approximately 20 g protein during and/or immediately after exercise is sufficient to maximize post-exercise muscle protein synthesis rates. Additional ingestion of large amounts of carbohydrate does not further increase post-exercise muscle protein synthesis rates when ample protein is already ingested. Dietary protein should be ingested during and/or immediately after cessation of exercise to allow muscle protein synthesis rates to reach maximal levels. Future research should focus on the impact of the timing of protein provision throughout the day on the adaptive response to more prolonged exercise training.